Progression of carotid intima-media thickness, visceral fat accumulation and metabolic derangement in people living with HIV initiating antiretroviral therapy: A prospective cohort study at Thailand’s tertiary care center - Thirajit Boonsaen; Winai Ratanasuwan; Boonrat Tassaneetrithep; Tanyaluck Thientunyakit; Jitsupa Wongsripuemtet; Shanigarn Thiravit; Phatharajit Phatharodom; Oranich Navanukroh; Mayuree Homsanit (PLoS ONE, 2025)
Background Combination antiretroviral therapy (ART) has extended life expectancy for people with HIV, but long-term treatment is associated with adverse changes in body composition and cardiovascular risk. We evaluated 36-month changes in adiposity, metabolic parameters, and carotid intima-media thickness (cIMT) in Thai adults initiating ART. Methods A prospective cohort of 132 ART-naïve adults was followed for 36 months. Assessments at baseline, 12, 24, and 36 months included anthropometry; body composition by bioelectrical impedance analysis (BIA) and dual-energy X-ray absorptiometry (DEXA); metabolic and renal indices; and bilateral carotid ultrasound. Longitudinal changes were analyzed using non-parametric tests, and correlations were examined between cIMT and body composition or metabolic measures. Results Virological suppression exceeded 90% and CD4 counts improved steadily. However, notable adiposity changes were observed. Median BMI and waist circumference increased (both p < 0.01); total fat mass rose by 6.7%; visceral adipose tissue (VAT) increased by 33%; and the android/gynoid ratio exceeded 1.0 by 24 months, reflecting central fat redistribution. Fasting glucose increased (p < 0.05) while HOMA-β declined (p < 0.05), indicating early β-cell dysfunction; lipid profiles remained stable. Mean cIMT increased across arterial segments, most prominently at the carotid bifurcations (right: 0.644 mm at baseline to 0.729 mm at 36 months; + 0.085 mm; left: 0.675 mm at baseline to 0.756 mm at 36 months; + 0.081 mm both p < 0.01). Right bifurcation cIMT correlated positively with BMI, waist circumference, VAT, fasting glucose, and total cholesterol (all p < 0.05). Conclusions Despite durable viral suppression and immune recovery, long-term ART was associated with central fat accumulation and progressive cIMT thickening, particularly at the carotid bifurcations. These findings underscore the need for cardiometabolic risk monitoring as part of routine HIV care to identify early changes that precede overt disease.